Encyclopedia of Electrochemistry 2006
DOI: 10.1002/9783527610426.bard070008
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur

Abstract: The sections in this article are Introduction Sulfur and Polysulfide Ions in Solution Nonaqueous Solvents Aqueous Solutions Electroreduction of Sulfur and Redox Properties of Polysulfides “Classical” Nonaqueous Solvents Liquid Ammonia Aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 112 publications
0
4
0
Order By: Relevance
“…Because low operating voltages are not a problem anymore, the Li/S batteries have recently been reviewed 1,2 and extensive studies have been performed on the electrochemical reduction of sulfur. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Nevertheless, the electrochemical reduction of sulfur used as a cathode reaction has been known to be complicated, and final products as well as reaction paths have not been elucidated.…”
mentioning
confidence: 99%
“…Because low operating voltages are not a problem anymore, the Li/S batteries have recently been reviewed 1,2 and extensive studies have been performed on the electrochemical reduction of sulfur. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Nevertheless, the electrochemical reduction of sulfur used as a cathode reaction has been known to be complicated, and final products as well as reaction paths have not been elucidated.…”
mentioning
confidence: 99%
“…Our simulation results show that unlike the CVs of Li 2 S 6 in DMF [22] and NH 3 , [23] the R 2 peak of Li 2 S 6 in 1 M LiTFSI in TEGDME : DOL corresponds to the simultaneous reductions of S 6 2− , S 4 * − and S 3 * − . Simulation results have also shown that the increase in the intensity and appearance of CV peaks during the second cycle as in the case of Li 2 S 8 and Li 2 S 6 solutions respectively, are due to the occurrence of additional electrochemical reactions and change in the polysulfide speciation at the end of the first cycle.…”
Section: Discussionmentioning
confidence: 71%
“…and Levillain et. al ., [23] respectively. The CVs of Li 2 S 6 in DMF consists of two reduction peaks namely R 4 and R 3 which correspond to reductions of S 4 * − and S 3 * − , respectively.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation